PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA POKOK BAHASAN DIMENSI DUA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI SMK AL-INABAH PONOROGO - Dina Okzolatavina; Senja Putri Merona (EDUPEDIA, 2018)
This research aimed to produce learning media using Macromedia Flash in subject discussion dimension 2. Other than that to find out the feasibility of interactive learning media based on criteria of validity, practicality and effectiveness. This learning media be developed because lack of student motivation and the absence of learning support media. This research is a development research. This development research use Plomp development model which consists 4 phases, there are (1) the initial investigation phase, (2) design phase, (3) realization/construction phase, (4) test, evaluation, and revision phase. The subject of the validity trial consisted of 1 media expert and 11 student of 11th grade multimedia SMK A-Inabah and for the subject of the effectiveness trial is 11 student of 11th grade multimedia SMK A-Inabah. Data collection tchniqyes using questionnaries. And the instruments used to collect data included media expert validation sheets, expert material validation sheet, teacher response questionnaire, student response questionnaire, and student learning motivation questionnaire on mathematics. Data analysis techniques are used to analyze validity and practicality in the form of quantitative data analysis and then converted to qualitative data. While to analyze the effectiveness of learning media using Wilcoxon non-parametric test. The result of this development study resulted that validity values of media experts and material experts meet the good criteria. For the practicality value from the teacher respondents meet the good criteria while from the students respondents meet the very well criteria. For the results of effectiveness shows that    and so  is rejected. Its means that students learning motivation after using media is better than students learning motivation before using the media. So that it can be concluded that the interactive learning media developed have fulfilled the validity, practicality, and effectiveness criteria